Eco-Epidemiologic Impacts of HPAI on Avian and Human Health in Egypt - Kaoud, H.A. (International Journal of Poultry Science, 2007)
In this article, trials for investigation and analysis were carried out to understand the ecological and the epidemiological aspects of AI problem in Egypt and its impacts on poultry and human health.135 different flock types (Broilers, Breeders, Layers, Ducks and Geese) as well as Roof-top and Back-yard raising birds from 18 different Governorates of Egypt were examined serologically for detection of Al antibodies during the period from Feb. 6th, 2005 to Feb. 6th, 2006. Farm and Governorate biosecurity measurers were analyzed and evaluated besides, the impacts of HPAI on human health. The results showed that Al virus antibodies were detected in roof-top and back-yard raising birds only (Fowls, Ducksand Geese) in percentages averaged 4%,10% and 2% in (EL Qualiobia, EL Dakahlia, Dimiatta, Cairo and Giza.) (EL Qualiobia, EL Dakahlia, Dimiatta, Cairo, Giza EL Menia, Beni-Seuif and Kafer EL Sheikh) and (EL Qualiobia and EL Behaira) respectively. The association between the biosecurity of the farms and the occurrence of AI infection during the epidemic strike, revealed: 3.76 relative risk, 0.69 attributable risk, 2.66 The association between governorates farm density and the occurrence of AI infection revealed: 1.29 relative risk, 0.15 attributable risk, 1.55 Omega magnitude and Ψ was 1.88.The impact of AI on human health in Egypt was analyzed through a retrospective study and a zoonotic epidemiological map was drew.